Exploration of the Effect of Tobacco Smoking on Metabolic Measures in Young People Living with HIV - Mark L. Rubinstein; D. Robert Harris; Bret J. Rudy; Bill G. Kapogiannis; Grace M. Aldrovandi; Kathleen Mulligan (AIDS Research and Treatment)
We conducted cross-sectional, multicenter studies in HIV-positive young women and men to assess metabolic and morphologic complications from tobacco smoking in 372 behaviorally infected HIV-positive youth, aged 14–25 years. Measurements included self-reported tobacco use, fasting lipids, glucose, fat distribution, and bone mineral density (BMD; dual-energy X-ray absorptiometry scans). Overall, 144 (38.7%) self-reported smoking tobacco and 69 (47.9%) of these reported smoking greater than five cigarettes per day. Smokers versus nonsmokers had lower mean total cholesterol (146.0 versus 156.1 mg/dL; P<0.01) and lower mean total body fat percent (24.1% versus 27.2%, P=0.03). There was no difference between smokers and nonsmokers in fasting glucose or BMD. There appear to be only minimal effects from tobacco smoking on markers of cardiac risk and bone health in this population of HIV-positive youth. While these smokers may not have had sufficient exposure to tobacco to detect changes in the outcome measures, given the long-term risks associated with smoking and HIV, it is critical that we encourage HIV-positive youth smokers to quit before the deleterious effects become apparent.